The Effect Of Work Stress, Job Satisfaction, And Organizational Commitment On Employees' Turnover Intention At Pt. Bank Sumut Head Office Medan - Siti Normi; Maludin Panjaitan; Septi Kristina Silalahi (International Journal of Business and Quality Research, 2025)
This study aims to determine and analyze work stress, job satisfaction, and organizational commitment to employee turnover intention at PT. Bank Sumut Head Office Medan. The type of data used in this study is a quantitative descriptive method. The research sample was 85 people. The analysis method used was multiple linear regression analysis. Based on the test results, it can be concluded that work stress is partially significant to turnover intention, work satisfaction is partially not significantly influential to turnover intention, and organizational commitment is not significantly influential. Work stress, job satisfaction, and organizational commitment significantly affect turnover intention. Work stress, job satisfaction, and organizational commitment can influence turnover intention by 63.2%; other variables or factors explain the remaining 42.8%.